Conceptualization of self-awareness in adults with acquired brain injury: A qualitative systematic review. Issue 8 (14th September 2022) - Sansonetti, Danielle; Fleming, Jennifer; Patterson, Freyr; Lannin, Natasha A.
ABSTRACT: Self-awareness is an important consideration in cognitive rehabilitation for clinicians working with individuals following acquired brain injury (ABI), with impaired self-awareness linked to poor outcomes. To appropriately target assessment and intervention for self-awareness, its theoretical foundation and definition must be considered. The aim was to identify the definitions, theoretical models and conceptual frameworks of self-awareness in adults with ABI, and how self-awareness is conceptualized within those models. A qualitative systematic review was completed using search terms related to descriptions of models/frameworks, ABI and self-awareness. Data were analysed by narrative synthesis. Thirty-five papers were included in the review. Within these, 13 models, 12 conceptual frameworks and 2 theories were described. The main themes and subthemes conceptualized in the synthesis were: Clinical presentation of self-awareness (classifications and dimensions of self-awareness), development of self-awareness (knowledge, feedback mechanisms, temporal aspects, self-evaluation, enablers, barriers), understanding (dys)function (cognitive processing mechanisms, neurological foundations, causal factors), and practice guidance (assessment and intervention). This review identified an extensive theoretical basis to support conceptualization of self-awareness following ABI, underpinned by a distinction between intellectual awareness, on-line awareness, and psychological denial. Clinical application of an evaluation process that includes these elements would be beneficial to inform the rehabilitation process.